Correlation of HbA1c levels and neutrophil-to-lymphocyte ratio (NLR) with wagner grade of diabetic foot ulcers in type ii diabetes mellitus patients undergoing treatment at Ibnu Sina Hospital in 2023 - Putri, Andi Iin T.C; Sommeng, Faisal; Nur, Muh. Jabal; Kartika, Irna Diyana; Purnamasari, Reeny (Institute Of Computer Science (IOCS), 2025)
Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or insulin resistance. HbA1c levels can reflect long-term glycemic control, while the neutrophil-to-lymphocyte ratio (NLR) serves as an inflammatory biomarker associated with disease severity in type II DM, including diabetic foot. This study is a descriptive analytic observational study with a cross-sectional design aimed at analyzing the relationship between HbA1c levels and NLR with Wagner’s grading of diabetic foot ulcers in type II diabetes mellitus patients. Among 34 diabetic foot patients, the majority were over 50 years old (94.1%), with a higher proportion of females (55.9%), an average HbA1c level of 9.33, and an average NLR of 9.31, indicating variations in glycemic control and systemic inflammation in ibnu sina Hospitak in januari until september 2023. Wagner's ulcer grade ranged from 2 to 4, with an average of 2.82, reflecting moderate to severe severity. Correlation analysis showed that HbA1c levels (r = 0.523, p = 0.002) and NLR (r = 0.602, p = 0.000) had a significant and positive relationship with diabetic ulcer severity. The study results indicate a significant correlation between HbA1c levels and NLR with Wagner’s grading of diabetic foot ulcers, where higher ulcer severity is associated with increased HbA1c and NLR levels due to greater insulin resistance.